Effect of feedback through dynamic assessment on EFL field-dependent and field-independent learners’ speaking skill development - Kafipour, Reza; Khoshnood, Ali (Frontiers in Education, 2023)
Introduction Testing and assessment tools evaluate students’ performance in a foreign language. Moreover, the ultimate goal of tests is to reinforce learning and motivate students. At the same time, instructors can gather information about learners’ current level of knowledge through assessment to revise and enhance their teaching. This study aimed to investigate the effect of Dynamic Assessment on Iranian English as a Foreign Language (EFL) learners’ speaking skills by considering language learners’ cognitive styles (field dependence and field independence). Methods For this purpose, 60 Iranian intermediate-level EFL female learners were selected through convenience sampling from three language institutes with similar teaching methods in Shiraz, Iran. The current study has a quasi-experimental design since randomization was impossible. First, the authors used the Nelson Proficiency test and interview to determine the participants’ proficiency level and speaking ability, respectively. Next, they took the group embedded figures test (GEFT) to determine the participants’ type of cognitive style (field dependence or field independence). Next, the participants were randomly assigned to two experimental (FD and FI learners with the dynamic assessment) and two control groups. Paired and independent-sample t-test were applied to analyze the data. Results and discussion Results revealed that although dynamic assessment was effective for both experimental groups, the Field-dependent group with dynamic assessment outperformed the other. Thus, it can be concluded that in addition to the dynamic assessment, language learners’ cognitive style can also play a vital role in increasing the assessment effectiveness. This type of assessment attracts instructors’ attention to learners’ potential to help the language learners gradually improve their performance. In addition, language institutes can introduce this new way of assessment in their advertisements and attract more students, leading to higher income and publicity for them.